EFEKTIVITAS PENAMBAHAN GARAM PADA PEMBUATAN TEMPOYAK DURIAN (Durio zibethinus Murr) SEBAGAI RANCANGAN LEMBAR KERJA PESERTA DIDIK DALAM PEMBELAJARAN BIOTEKNOLOGI DI SMA - Putri Ramadhani; Imam Mahadi; Zulfarina Zulfarina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Tempoyak is a typical traditional food from Bengkulu which is from durian fruits meat the making of tempoyak is arded by addition of salt, but salt concentration is not known by the public. The research aims to determine effectiviness of salt addition to the quality of tempoyak durian (Durio zibethinus Murr) and produce the design of biology student worksheet in hight school class XII Biotechnology subject. Experimental research by conducting tempoyak durian fermentation experiment with the addition of 1 gram, 2 grams, 3 grams, 4 grams and 5 grams with 5 treatments of 3 repetitions of 200 gram durian and continued with the development of student worksheet learning from experimental research data (only at the Analysis and Design stage). The results showed that the addition of salt to tempoyak durian had an effect on the decrease in pH value. The lowest pH value for salt addition was in A2 and A3 treatments, while in A4 treatment it increased to an average pH value of 4.4 which had an organoleptic value in brownish yellow color, flavored tempoyak and stinging, slightly salty and slightly acidic and soft texture. The results of this study can be used as learning resources oriented to the Project Based Learning model of Biology subjects in class XII biotechnology material. All data from the research results can be used to design the Senior High School Biology student worksheet Learning in Conventional Biotechnology class XII with Project Based Learning Learning Models. However, before the student worksheet design is used on a broader scale it is recommended that a feasibility test and effectiveness be carried out on a limited scale.Key Words: Durio zibethinus Murr, Tempoyak, Salt, Student Worksheet